Examining the Effect of the Missouri Mathematics Project Learning Model on Junior High School Students’ Learning Motivation - Nuryahya, Rifqi; Khuzaini, Nanang (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
This study examines the effect of the Missouri Mathematics Project (MMP) learning model on the mathematics learning motivation of seventh-grade students at SMP Negeri 1 Sedayu. A quasi-experimental method with a nonequivalent control group design was employed. The participants consisted of two classes: class VII B as the experimental group implementing the MMP model and class VII D as the control group receiving conventional instruction, involving 31 and 32 students respectively. Students’ learning motivation was measured using a validated motivation questionnaire. Data were collected through pretest and posttest administrations and analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, paired sample t-test, and independent sample t-test at a 5% significance level. The results indicate that the Missouri Mathematics Project learning model did not produce a significant improvement in students’ learning motivation. The experimental group showed no significant motivational gain after the intervention, while the control group demonstrated a higher increase in learning motivation through conventional instruction. Differences in learning motivation between groups were influenced by students’ internal and external factors. These findings suggest that although the Missouri Mathematics Project effectively supports structured cognitive learning, it has not yet optimally addressed affective aspects such as learning motivation. Therefore, the integration of explicit motivational strategies is necessary to enhance students’ engagement in mathematics learning.